أثر المكان على السياحة (Journal of Engineering, 2013)
Most communities seek, which possesses a cultural legacy to communicate with the past and to reach the best possible legislation to help them protect their cultural. Tourism as the economic development based on the data in light distinct places, including  traditional and historical environments requiring activated and revived in my adopting the concept of transnational Revival Tourism. Through the survey data in environments where conventional and (historical - Sensationalism) theoretically and practically, it was drawn from a number of indicators truth spatial phenomenon and the phenomenon depends show and try on a number of variables and interventions including historical and philosophical interpretations of those facts, in addition to theoretical and policy orientations or local government. Those indicators were tested on four samples were Aleppo castle and its surroundings, and the old city of Aleppo and its surroundings, adopted by the state of research as a cultural one and intertwined with historical and archaeological values and traditional surroundings, to explore the values underlying facts percentage-active (frozen), which show depends on the ability and activate planned and designed urban and domestic policies on the understanding and use of historian , archeologist and sociologists. . The percentage values College Library 42% in the four samples relative values but they must be significant and have an impact in increasing the visibility and location in the event activated.